2013
DOI: 10.1371/journal.pone.0074497
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Psychological Stress Induces the Accumulation of Myeloid-Derived Suppressor Cells in Mice

Abstract: Chronic psychological stress has been shown to adversely impact immune system functions and compromise host defenses against various infections. However, the underlying mechanisms remain elusive. Recent studies have demonstrated that myeloid-derived suppressor cells (MDSCs) play an important role in regulating immunity. It is of interest to explore whether or not chronic psychological stress plays immunosuppressive functions partially by inducing MDSCs accumulation. In this work, we report that chronic psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…However, new data suggests that stress alone can lead to the accumulation of MDSCs, which are broadly defined as CD11b + GR1 + cells. Jin et al demonstrated that these cells have the potential to suppress immunity by producing factors such as nitric oxide and arginase [84]. These studies are in agreement with others showing a strong correlation between stress and immune suppression in breast cancer patients [85].…”
Section: Stress and Immunosuppressionsupporting
confidence: 82%
“…However, new data suggests that stress alone can lead to the accumulation of MDSCs, which are broadly defined as CD11b + GR1 + cells. Jin et al demonstrated that these cells have the potential to suppress immunity by producing factors such as nitric oxide and arginase [84]. These studies are in agreement with others showing a strong correlation between stress and immune suppression in breast cancer patients [85].…”
Section: Stress and Immunosuppressionsupporting
confidence: 82%
“…Our data demonstrates that a single IV dose of MSCs shortly following injury reversed the BM dysfunction seen following LC/CS and resulted in an increase in both BM cellularity and HPC growth within the BM to levels observed in naïve animals. The role of MSCs on the BM microenvironment has been studied in the setting of co-transplantation with HPCs and in autoimmune diseases marked by chronic inflammation 1719 . When MSCs are co-transplanted with HPCs at the time of BM transplantation, they enhance the speed of recovery and reduce the incidence of graft-versus host disease (GVHD) 1718 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are very few studies demonstrating myelopoiesis in chronic stress models outside of RSD, whereas certain models reduce microbial activity. For example, several studies investigated the immune response to chronic restraint stress and reported diminished natural killer (NK) cell function, cytokine secretion, and enhanced viral replication (Hunzeker, Padgett et al 2004, Tseng, Padgett et al 2005, Jin, Wang et al 2013.…”
Section: Rsd-responsive Neuroendocrine Pathways Alter Homeostatic Hemmentioning
confidence: 99%